Women constructing careers and identities in masculine arenas - Tiihonen, Donna (2025)
The context of this research is the career development of women in high professional positions in the field of STEM. This research will describe their career development paths, and thus increase the knowledge of how women’s careers are constructed in STEM, which has typically been seen as a male-dominated sector. In addition to describing women’s career development paths, the construction of their identity is also explored. Both perspectives, career development, and identity, will help to understand why so few women are in management positions within organizations. The research is conducted in a company that operates globally in the technology sector. Women with current or past experience working for the organization have been invited to participate in the research. This includes 11 women, both in management positions and various expert roles. The research uses a qualitative approach, with a strong emphasis on narrativity, allowing women to naturally reflect on their career actions and helping the researcher understand their behavior through theme-centered interviews. Particularly, women who have chosen to build their careers in STEM can provide valuable information on their mechanisms to succeed in the field. Research results show that women’s careers in STEM can be seen as cyclical, involving different stages, emerging and ordered patterns, breaks, and challenges. By having the narrative approach, women’s career stories highlight that career development is a very personal and unique journey. This research challenges existing theories of women’s career development which are often based on models designed for men. Using a narrative approach in research offered an excellent way to deeply understand women’s careers and their perspectives on their own career paths. Therefore, narrativity will have the potential to offer much more in future research as well.